The decade ahead applications and contexts of motivation and achievement - Urdan, Timothy C.; Karabenick, Stuart A. (Emerald, 2010)
Volume 16 of Advances in Motivation and Achievement is presented in two books. In both books, leading researchers in the field review the current state of the knowledge in their respective sub-disciplines and offer their prognostications about where the research is likely to proceed in the decade ahead. In this book, Volume 16B, chapters examining the associations between motivation and other constructs, such as emotion and self-regulation, are presented. In addition, Volume 16B includes chapters examining sociocultural approaches to the study of motivation, the motivation of African American students and teachers' motivation, the application of motivation research in classrooms, and the policy implications of motivation research. In the first book, Volume 16A, seven prominent theories of motivation are examined, including research on self-efficacy, achievement goal theory, expectancy-value theory, self-determination theory, self-concept research, implicit motives, and interest. By providing chapters that both summarize and look forward, the two books in this volume offer a useful roadmap for the future of motivation research in a variety of areas.
Description based on print version record.
Keywords: Motivation in education.; Educational psychology.; Learning.; Psychology -- Education & Training.; Education -- Educational Psychology.; elektronické knihy; electronic books